Discovery of N-(2-Aminophenyl)-4-(bis(2-chloroethyl)amino)Benzamide as a Potent Histone Deacetylase Inhibitor - Zhang, Lihui; Li, Xiaoyang; Chen, Yiming; Wan, Minghui; Jiang, Qixiao; Zhang, Li; Chou, C. James; Song, Weiguo; Zhang, Lei (Frontiers in Pharmacology, 2019)
Inhibition of HDACs have been an important emerging therapy for the treatment of multiple cancers. However, the wide application of HDAC inhibitors is restricted by the limited potency against solid tumors. In order to discover novel HDAC inhibitors with potent antitumor activities, nitrogen mustard group was introduced to the structure of CI994. The derived molecule N-(2-aminophenyl)-4-(bis(2-chloroethyl)amino)benzamide (NA) exhibited enzyme inhibitory pattern of class I selectivity with IC50 values of 95.2 nM, 260.7 nM and 255.7 nM against HDAC1, HDAC2 and HDAC3, respectively. In the antiproliferative assay, NA exhibited 10.3-fold (2.66 μM) and 11.3-fold (1.73 μM) higher potency than SAHA (27.3 and 19.5 μM) in inhibition the growth of A2780 and HepG2 cells, respectively. Further HepG2 cell based cell cycle and apoptosis studies revealed that induction of G2/M phase arrest and cell apoptosis makes contributions to the antitumor effects of NA. It is suggested that NA could be utilized as a lead compound in the development of bifunctional HDAC inhibitors for the treatment of solid tumors.